Ethics from a Feminist Perspective - Tan, Jean Emily P (Archīum Ateneo, 2020)
In this two-part lecture, Doc Jean discusses Philosophy from the lens of a meta-ethical feminist critique. Speaker: Jean P. Tan is an Assistant Professor of Philosophy at Ateneo de Manila University. She received her doctorate from Loyola University Chicago, where she wrote her dissertation on Sarah Kofman. She has served as the Editor of Budhi: A Journal of Ideas and Culture. She teaches a variety of philosophy courses, among which is a course on feminist thought.